Penguatan Kepemimpinan Visioner Dan Kepuasan Kerja Dalam Upaya Peningkatan Organizational Citizenship Behaviour - Tristan Kusumawati Alexandra; Soewarto Hardhienata; Herfina Herfina (Universitas Pakuan, 2023)
THE STRENGTHENING VISIONARY LEADERSHIP AND JOB SATISFACTORY TO IMPROVE ORGANIZATIONAL CITIZENSHIP BEHAVIOURAbstract. The purpose of this study was to empirically determine the improvement of Organizational citizenship behaviour. Research respondents were permanent teachers at private elementary school in Bogor city. The number of samples were 121 teachers who were established by using proportional random sampling technique. The method used was the correlational method. Hypotheses testing was carried out by using parametric statistical analysis in the form of linear regression analysis, correlation analysis, and partial analysis where a significance level of α = 0,01 and α = 0,05. The research came up with three conclusions. Firstly, there was a very significant positive relationship between the visionary leadership and Organizational citizenship behaviour where the correlation coefficient of ry1 =0.764. Secondly, there was a very significant positive relationship between job satisfactory and Organizational citizenship behaviour, where the correlation coefficient of ry2 =0.779. Thirdly, there was a very significant positive relationship between the visionary leadership and job satisfactory together with the organizational citizenship behaviour, where the correlation coefficient of ry.12 = 0.764. Based on the results of the research, it can be concluded that the Organizational citizenship behaviour can be enhanced by strengthening the visionary leadership and job satisfactory. Results of the SITOREM analysis indicated that several priority indicators need to be improved, such as work characteristics, colleagues, formulate the vision, future vision, persistent, and altruism. Based on the results above, it can be concluded that Organizational citizenship behaviour can be enhanced by strengthening the visionary leadership and job satisfactory..